Komodo dragon vs. king cobra by Jerry Pallotta ; illustrated by Rob Bolster. - Pallotta, Jerry (New York Scholastic, 2011)
Contains facts about komodo dragon and king cobra, comparing such aspects as their sizes, brain structure, and abilities.
Ages 4-9